The Analysis of Nutritional Status of The Kadirejo Village Community as A Supporting Factor for The Sports Development Index of Semarang Regency - agus; Noor Aliffian Reckyantha, Naufal; Rizqiyatul Hidayah, Wahyu; Amalya, Permata; Arju Azmanaja, Diva; Jelang Ramadhan, Fiar; Amin, Nur (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Nutritional status is one of the important factors that affect the level of fitness and community participation in sports activities. This study aims to find out how the nutritional status of the people of Kadirejo Village plays a supporting factor in increasing the Sports Development Index (IPO) of Semarang Regency. This study uses a quantitative descriptive method with a cross-sectional approach. The sample in this study is the people of Kadirejo Village as many as 29 people who were selected by purposive sampling technique. The research instruments include a scale to measure weight, a microtoice to measure height and a formula (BMI) to measure nutritional status. The results of the study showed that there were 14 respondents with normal nutritional status (48.28%), nutritional status of more than 9 people (31.03%), lack nutritional status of 4 people (13.79%) and obesity 2 people (6.90%). The conclusion of this study is that most of the people of Kadirejo Village have normal nutritional status. Which supports factors in the increase in the Sports Development Index (IPO) of Semarang Regency.